Analysis of Profits and Development Strategies for Broiler Chickens in Mitra Pokphand Chicken Farms - Putra, Rico Mandana; Harahap, Uun Novalia; Utama, Denny Walady (Journal of Engineering Science and Technology Management (JES-TM), 2024)
It is known that the income earned by breeders is still not optimal, so it is quite difficult to obtain higher profits. Based on the problems in this study, how to analyze factors of production, total costs, income, business efficiency and Break Event Point broiler farms in partnership Pokphand chickens and how business development strategies can be applied. This study aims to analyze the advantages of Mitra Pokphand Chicken Livestock to then determine the right development strategy by utilizing the strengths and opportunities that this livestock business has. Data analysis was carried out qualitatively and quantitatively. The data that has been obtained is analyzed using descriptive analysis, business analysis and SWOT analysis using the IFE/EFE matrix. The results showed that the size of Mitra Pokphand's business income was influenced by revenue and production costs. For breeders to increase their income, it is hoped that livestock owners can reduce production costs. Meanwhile, based on the SWOT analysis IE matrix, the broiler business in Mitra Pokphand Chicken Livestock is in cell IV position which indicates that the strategy needed for the business is to grow and develop (growth and build). This strategy shows that livestock businesses need strategies to grow better and to develop broiler farming businesses to be better.